Resistance and Disruption: Women at the University of Michigan-Flint 1956-1966. - Laube, Heather (Women's Studies, 2018)
The article discusses the perseverance by working-class women to pursue a college degree at the Flint College of the University of Michigan and advance their career in the 1950s and 1960s to help advance their families into middle-class status. Also cited are the good employment in the auto industry during the period, how the first women graduates at the school disrupted gender expectations, as well as the emergence of the civil rights movement and career women in the 1960s.